Nursing Students' Experiences in Intensive Care Practice: A Qualitative Study - Dural, Gul (Wiley, 2025)
Background: Patients in intensive care units (ICUs) may experience physical, mental, social and spiritual suffering. The practice experiences of nursing students in the intensive care unit will significantly impact their acquisition of professional skills and future professional practice. However, nursing students often encounter challenges during their clinical internships. Aim: This study explores the experiences of nursing students in intensive care settings. Study Design: This qualitative descriptive study was conducted with 15 nursing students in clinical practice in the intensive care units of a university hospital in eastern Turkey. The researcher created two forms to meet the purpose of the study. The first form gathered demographic information about the participants and the second form contained semi-structured interview questions. Thematic analysis was used to evaluate the data. Ethics committee approval was obtained. Results: Ten of the students were female and five were male. They were between 20 and 24 years old and were second-year nursing students. Thematic analysis revealed four main themes and nine sub-themes. The identified themes were: (1) professional competence, (2) emotional changes, (3) challenging situations and (4) influential events. Conclusion: This study revealed that nursing students experience significant emotional difficulties while developing professional skills during their intensive care internships. The findings suggest that, although students benefit from these experiences, they require more structured support systems. Effectively and supportively planning intensive care internships is important for improving the quality of education and strengthening students' psychological resilience. Relevance to Clinical Practice: This study highlights the key challenges and learning needs of nursing students in critical care settings, providing important information for critical care nurses. Even in countries where students do not complete an internship in critical care, the findings support developing orientation, mentoring and emotional support systems for newly graduated nurses. A supportive learning environment that strengthens the connection between theory and practice is essential for the learning process and patient safety.